Identification and mapping of migration routes of transhumance communities using Geographic Information System in the Western Mediterranean Region in Turkey - Tolunay A.; Turkoglu T.; Kasikci D.; Daskiran I.; Ozmis M. (Pastoralism and sustainable development: proceedings, 2021)
Turkey's nomads, replaced periodically to graze their goats in the basin of the Mediterranean Region for many years. Hair goat breeding for nomads is both a production system and a cultural value symbol. Nomads who drives the immigrant life style, has come to the Turkish water front. Economy for nomads is based on animal breeding. Geographical mobility and animal breeding are two important factors affecting and shaping the nomadic life style. During these migrations, animals have to graze every day at certain times. For this reason, they cannot travel continuously. For this reason, migrants cannot travel more than 4-5 hours per day. The roads on the Taurus Mountain are generally available, but do not provide access to thousands of animals. The study site is located between 31°4'10 "and 38°27'50" northern latitudes and between 32°33'48 "and 36°3'30" east longitudes. The migratory routes of livestock farming communities from Geographical Information Systems (GIS), ArcGIS package program and Google Earth program. In addition to these, topographical maps and landscaping plans and maps of the Isparta and Antalya Forest Regional Directorates will be utilized. With multifunctional GPS, coordinate values (including x, y values) and length measurement of migration paths can be saved and uploaded as data to related programs. All the data obtained with these maps and observations were transferred to the computer with the GPSTrackMaker program and important points were determined and the migration paths were drawn with the joining of points (vector). According to the migratory patterns made by the nomads, "Small Ruminant Operation Types" were determined. These were (1) Small Scale Sheep Enterprises, (2) Large Scale Sheep Enterprises, (3) Small Local Migration Mixed Farming Enterprises, (4) Long Distance Regional Migrations Goat Enterprises.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)